Analisis Biaya dan Pendapatan Budidaya Jamur Tiram Putih di UMKM Jamur Betuah Kota Pekanbaru - Ahmad Guswandi; Dini Amalia Putri (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
Indonesia's agricultural sector plays a vital role in food security, increasing community income,and improving nutrition through food diversification. One of its main subsectors is horticulture,with white oyster mushrooms (Pleurotus ostreatus) as a high–economic–value commodity whosedemand continues to rise. This study analyzes the costs and income of white oyster mushroomcultivation at UMKM Jamur Betuah in Pekanbaru through field observation, interviews, andquantitative descriptive analysis. From 1,500 baglogs, a total of 950 kg of mushrooms areproduced per cycle, with total production costs of IDR 57,133,600 and revenue of IDR375,000,000, resulting in a net income of IDR 317,866,400. The Break Even Point (BEP) analysisof 0.15 indicates that the break-even point can be reached at a low production level. These findingsconfirm that white oyster mushroom cultivation at UMKM Jamur Betuah has strong economicprospects and is feasible to develop as a sustainable agribusiness.